2016
DOI: 10.1007/978-3-319-18497-5_49
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cerebral Edema via an Osmotic Transport Device Improves Functional Outcome after Traumatic Brain Injury in Mice

Abstract: Traumatic brain injury (TBI), the foremost cause of morbidity and mortality in persons under 45 years of age worldwide, leads to about 200,000 victims requiring hospitalization and approximately 52,000 deaths per year in the United States. TBI is characterized by cerebral edema leading to raised intracranial pressure, brain herniation, and subsequent death. Current therapies for TBI treatment are often ineffective, thus novel therapies are needed. Recent studies have shown that an osmotic transport device (OTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that, through establishing an external osmotic gradient, water can be removed from the brain in a controlled manner under normal and pathological brain swelling conditions. Such an “osmotic treatment device” (OTD) was able to reduce brain tissue water content and improve neurological outcome in mouse models of cytotoxic edema and traumatic brain injury without causing histological damage [ 118 , 119 , 120 ]. These results established proof-of-principle for the concept of direct osmotherapy for the treatment of CNS edema.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…It has been demonstrated that, through establishing an external osmotic gradient, water can be removed from the brain in a controlled manner under normal and pathological brain swelling conditions. Such an “osmotic treatment device” (OTD) was able to reduce brain tissue water content and improve neurological outcome in mouse models of cytotoxic edema and traumatic brain injury without causing histological damage [ 118 , 119 , 120 ]. These results established proof-of-principle for the concept of direct osmotherapy for the treatment of CNS edema.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…We have recently demonstrated that through establishing an external osmotic gradient, water can be removed from the brain in a controlled manner under normal and pathological brain swelling conditions. We found that the OTD reduced tissue water content and dramatically improved neurological outcome in an acute mouse models of cytotoxic edema and traumatic brain injury (TBI induced by controlled cortical impact, CCI) without causing histological damage ( McBride et al, 2012 , 2014 , 2016 ). These results established proof-of-principle for the concept of direct osmotherapy for treatment of CNS edema.…”
Section: Introductionmentioning
confidence: 97%
“…There is, therefore, a need for new methods to effectively ameliorate edema following SCI in order to minimize spinal cord compression, decrease ISP at the injury site, improve vascular perfusion (SCPP), and improve neurological outcome. In this work we develop our currently effective osmotic transport device (OTD) that has been shown to improve outcome in global and focal models of cerebral edema ( McBride et al, 2012 , 2014 , 2016 ) and apply it to SCI in a well-accepted rodent model of thoracic contusion SCI.…”
Section: Introductionmentioning
confidence: 99%